Thermal comfort conditions of shaded outdoor spaces for local and international students at Universiti Putra Malaysia, Serdang - Makaremi, Nastaran (2011)
In the recent years, the accelerated rate of urban growth in tropical cities highlights the critical necessity of creating more outdoor environments for leisure and recreation activities of citizens. Nevertheless, the outdoor thermal environment and the actual thermal sensation of users as subjective parameters have not been fully explored in outdoor environments of hot and humid climate. This fact elucidates the need for exploring human thermal comfort in outdoor spaces within hot and humid tropical climate, taking into account the objective microclimatic parameters and the human subjective responses. Consequently, in this research, a quantitative field study research method was applied to investigate the thermal comfort conditions of outdoor environments in hot and humid tropical climate of Malaysia. The study concentrated on the thermal conditions of shaded outdoor spaces in Universiti Putra Malaysia campus and thermal sensation of individuals using these spaces. Correspondingly, the thermal conditions of outdoor spaces are evaluated based upon the measurement of major microclimatic parameters (air temperature, relative humidity, wind speed and mean radiant temperature), while the actual thermal perception of users was captured simultaneously using a questionnaire survey. The study focused on the students of university including local and international students as the respondents. Meanwhile, this research utilized the appropriate outdoor thermal comfort index, entitled Physiologically Equivalent Temperature (PET) to assess the conditions of human thermal comfort in different outdoor spaces of study area. Results from this study indicated that both environmental and human parameters contribute considerably to the condition of the human thermal comfort in outdoor spaces. Thus, this fact reflects that thermal comfort approaches must be analyzed according to human parameters and subjective responses as well as objective environmental parameters in order to understand the complexity of thermal comfort conditions in outdoor environment. Consequently, the study also found that there is a significant difference between the thermal comfort perceptions of local and international individuals. These findings confirmed the poor tolerance of international students and the influential effects of adaptation and acclimatization of local students regarding the specific climatic conditions of the region. The finding of this study could be applied in the design decision-making concerning outdoor spaces for creating thermally comfortable environments which could lead to increasing the usage of outdoor spaces. In conclusion, the final outcome of study contributes towards improving the outdoor thermal comfort conditions of users within hot and humid tropical contexts to enhance the quality of outdoor life in urban area.